Occupational risk factors for lung cancer: A population-based case-control study in British Columbia - Yenugadhati, Nagarajkumar (University of Ottawa (Canada), 2007)
Occupational carcinogens have been linked to lung cancer: among 74 known occupational carcinogens and carcinogenic circumstances, 37 have been associated with lung cancer. We report on a large population-based case-control study in British Columbia (2998 lung cancer cases). In the absence of a non-cancer control group, patients with cancers other than lung cancer (11,737) served as controls. Logistic regression, adjusted for smoking history, was used to examine occupationally related lung cancer risk with histological subtypes. Elevated risk was found in several occupational circumstances: metal working, mining, deck crew of ship, bakers, workers in electric power systems, construction workers (all histological types), chefs and cooks (large cell carcinoma only), and medical workers (large cell carcinoma only). Odd ratios varied from 1.6 to 4.6, with most being around 2.0. Potential exposures found in these high risk occupational groups which warrant further evaluation include: formaldehyde, radiation, electromagnetic fields, wood dust, and cooking fumes.
Keywords: Health Sciences, Occupational Health and Safety.; Health Sciences, Public Health.; Health Sciences, Oncology.